KOMPETENSI ALUMNI PG PAUD FIP UNNES DI LEMBAGA PENDIDIKAN - Edi Waluyo, Lita Latiana, Decik Dian Pratiwi (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
Education is very important for the development of early age children and in the education process, they should be cared by profesional teachers. This study aimed at identifying the competence of the graduates from PG PAUD FIP UNNES located in Central Java. Applying survey method, the study collected data using questionnaire to be analyzed with descriptive statistics. The results showed that the graduate competence belongs to the high category. However, the existing competence still needs to be further developed to maximize the role of early childhood education institutions.